2021
DOI: 10.3390/pathogens10040480
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Acinetobacter baumannii Resistance and Hospital Use of Meropenem, Cefepime, and Ciprofloxacin: Time Series Analysis and Dynamic Regression Models

Abstract: Acinetobacter baumannii is one of the most difficult-to-treat pathogens worldwide, due to developed resistance. The aim of this study was to evaluate the use of widely prescribed antimicrobials and the respective resistance rates of A. baumannii, and to explore the relationship between antimicrobial use and the emergence of A. baumannii resistance in a tertiary care hospital. Monthly data on A. baumannii susceptibility rates and antimicrobial use, between January 2014 and December 2017, were analyzed using tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Serbia's national guideline for COVID-19 treatment (provided in Supplementary Table S3) emphasizes the absolute avoidance of antibiotic use precisely because of the risk of rising AMR. Moreover, in-hospital use of antibiotics has known to be a driver of resistance in a time-dependent manner [39], pointing to a need for rational use of antimicrobials across all levels of care.…”
Section: Discussionmentioning
confidence: 99%
“…Serbia's national guideline for COVID-19 treatment (provided in Supplementary Table S3) emphasizes the absolute avoidance of antibiotic use precisely because of the risk of rising AMR. Moreover, in-hospital use of antibiotics has known to be a driver of resistance in a time-dependent manner [39], pointing to a need for rational use of antimicrobials across all levels of care.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the articles 13 (22.3%) were published in China [ 21 , 25 28 , 42 , 60 , 62 64 , 68 , 72 , 77 ], 4 (6.9%) Europe [ 48 , 49 , 74 , 75 ], 4 (6.9%) South Korea [ 31 , 54 , 61 , 65 ], 4 (6.9%) Serbia [ 34 , 36 , 39 , 52 ], 3 (5.2%) Japan [ 20 , 30 , 40 ], 2 (3.4%) Italy [ 22 , 33 ], 2 (3.4%) Thailand [ 35 , 57 ], 2 (3.4%) France [ 46 , 56 ], 2 (3.4%) Spain [ 43 , 59 ], 2 (3.4%) Slovenia [ 47 , 71 ], 2 (3.4%) Switzerland [ 45 , 70 ], and the rest were in different countries [ 23 , 29 , 32 , 37 , 38 , 41 , 44 , 50 , 51 , 53 , 55 , 58 , 66 , 67 , 69 , 73 , 76 , 77 ]. The majority of the articles 11(23.4%) were published in 2017 [ 22 , 33 , 36 , 44 , 47 , 48 , 52 , 56 , 59 , 64 , 67 ], 2018 […”
Section: Resultsmentioning
confidence: 99%
“…Such observation indicates the significant shift of resistance profiles with COVID-19, and may be attributed to the inability to completely conform with standard practices of infection control during such unprecedented time ( Pascale et al., 2021 ). Also, the in-hospital use of antibiotics has known to be a driver of resistance in a time-dependent manner whether or not a pandemic takes place, highlighting the need for rational antimicrobial use across all levels of healthcare ( Kousovista et al., 2021 ), and this indeed, applies to carbapenems. In one retrospective single-center, case-control study, authors from Spain reported that COVID-19 patients had increased risk of nosocomial infections with carbapenemase-producing Enterobacteriaceae , with infections being severe, appearing in critically-ill patients, and associated with a high mortality.…”
Section: Carbapenemase-producers Causing Co-infections In Covid-19 Pa...mentioning
confidence: 99%